2013
DOI: 10.1371/journal.pone.0061058
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Iron Concentration May Influence Aging Process by Altering Oxidative Stress in Tissues of Adult Rats

Abstract: Iron is an essential element. However, in its free form, iron participates in redox-reactions, leading to the production of free radicals that increase oxidative stress and the risk of damaging processes. Living organisms have an efficient mechanism that regulates iron absorption according to their iron content to protect against oxidative damage. The effects of restricted and enriched-iron diets on oxidative stress and aging biomarkers were investigated. Adult Wistar rats were fed diets containing 10, 35 or 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 74 publications
3
33
1
Order By: Relevance
“…In particular, aged animals fed 2×BCAA exhibited a lower iron status in skeletal muscle. Similar to previous findings (D’Antona et al 2010; Arruda et al 2013), LI and 2×BCAA diets did not alter body mass of old rats, and muscle mass values were not changed by the dietary treatments.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…In particular, aged animals fed 2×BCAA exhibited a lower iron status in skeletal muscle. Similar to previous findings (D’Antona et al 2010; Arruda et al 2013), LI and 2×BCAA diets did not alter body mass of old rats, and muscle mass values were not changed by the dietary treatments.…”
Section: Discussionsupporting
confidence: 90%
“…Based on previous reports that LI (Otogawa et al 2008; Naito et al 2011; Arruda et al 2013) and BCAA (Iwasa et al 2013; Korenaga et al 2015) diets decrease tissue iron status in various iron overload conditions, we examined whether LI and/or 2×BCAA diets would alter the muscle iron status. The main effect of 2×BCAA diets on non-heme iron concentration level of the aged plantaris approached statistical significance ( P = 0.059; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of iron in basal ganglia is probably associated with neuronal death leading to Alzheimer disease, Parkinson disease, epilepsy, Huntington disease, dementia with Lewy bodies, and multiple sclerosis [4][5][6][7][8]. It was reported that iron participates in redox reactions, and catalyzes the formation of reactive oxygen species responsible for oxidative stress and damaging processes [9][10][11].…”
Section: Introductionmentioning
confidence: 99%